Gender Differences in Health-Related Quality of Life (HRQL) of Overweight and Obese Adults in a Representative Sample of Greek Urban Population - Ioannis Vrettos; Panagiota Voukelatou; Evelina Pappa; Chrysoula Beletsioti; Dimitris Niakas (Tehran University of Medical Sciences, 2021)
Background: The main objective was to investigate the relationship between Health-Related Quality of Life (HRQL) and Body Mass Index (BMI) status according to gender in a representative sample of Greek urban population. Methods: In this cross-sectional study, data were collected from 1060 participants (mean age 47.10 yr, 95%CI 46.09-48.07, 52.7% females) in a stratified sample of representative urban population during 1-20 Apr 2016 in Athens, Greece. Socio-demographic characteristics and medical history were involved. BMI (kg/m2) was calculated, based on reported height and weight. HRQL was assessed by using the Greek version of SF36. Parametric tests and multiple logistic regression analysis were applied to identify whether socio-demographic characteristics differed across BMI groups. Mann-Whitney test was used to detect significant differences in SF36 scales between men and women across different BMI and age groups. Μultivariate stepwise linear regression analyses were performed to investigate the influence of sociodemographic variables on HRQL. Results: The effect of being overweight or obese differs by age and gender and that this negative impact in HRQL was greater in women than in men. More vulnerable were overweight young and obese middle-aged woman both in terms of physical and mental health. On the other hand, HRQL of normal weight men and women did not differ in almost all age groups. Conclusion: Gender differences on HRQL observed in the general population were mediated by the different way that the two genders affected by increases in body weight.